A study on the effectiveness of window display in attracting customers to Fokus Store Pantai Dalam / Youssaineir Mohamed Yusof - Mohamed Yusof, Youssaineir (1998)
NRC DISTRIBUTION SDN BHD (Formerly known as Pernas Edar Sdn. Bhd.) has developed one step further suitable with its privatization by forming Fokus Banner Store franchise. The new type of retail store is trying to change people perception of how retail industry in Malaysia. Scope of this study however will focus on the effectiveness of window display in attracting customer’s attention. Through the observation the management need to improve their promotion technique especially for the window display Several changes could make the store look more attractive.